2018
DOI: 10.1097/j.pain.0000000000001361
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of angiotensin II type 2 receptor stimulation in vincristine-induced mechanical allodynia

Abstract: Peripheral neuropathy is the major dose-limiting side effect of many currently used chemotherapies, such as vincristine (VCR). We recently demonstrated that candesartan, an angiotensin II type 1 receptor antagonist, was neuroprotective against resiniferatoxin-induced sensory neuropathy, and that this effect is mediated by stimulation of the angiotensin II type 2 receptor (AT2R). Thus, we evaluated the effect of preventive treatment with candesartan and a specific AT2R agonist, C21, on a mouse model of VCR-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 52 publications
4
25
0
Order By: Relevance
“…Other investigations support Shepherd's findings. For instance, ARBs showed anti-allodynic effects in animals with vincristine-and paclitaxel-induced neuropathic pain [7,25]. In our cohort of patients, the level of bioinflammatory markers, NLR and MLR did not differ significantly amongst ACEi and ARB treatment groups when compared to no treatment, again supporting the lack of efficacy of ARBs on inflammatory pain even after excluding patients taking NSAIDs.…”
Section: Discussionsupporting
confidence: 56%
“…Other investigations support Shepherd's findings. For instance, ARBs showed anti-allodynic effects in animals with vincristine-and paclitaxel-induced neuropathic pain [7,25]. In our cohort of patients, the level of bioinflammatory markers, NLR and MLR did not differ significantly amongst ACEi and ARB treatment groups when compared to no treatment, again supporting the lack of efficacy of ARBs on inflammatory pain even after excluding patients taking NSAIDs.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, the clear evidence that AT 2 R agonism suppresses oxidative stress (ROS/ RNS) in neurons and glia that can prevent TRPA1 activation, and that neither DRG-neuronal nor peripheral-macrophage AT 2 R activate TRPA1 (the mediator of mechanical and cold hypersensitivity) in these cells, questions whether AT 2 R is actually a pain inducer for neuropathic pain. This contention is supported by recent studies which demonstrate that the nonpeptide AT 2 R agonist Compound 21 is protective against vincristine-induced neuropathic pain (Bessaguet et al, 2018). The same group had earlier demonstrated that the beneficial effects afforded by the AT 1 R blocker candesartan in resiniferatoxin-induced neuropathic pain were due to generation of Ang II and stimulation of the AT 2 R (Bessaguet et al, 2017).…”
Section: At 2 R-mediated Nociceptive-and Anti-nociceptive Actions: a mentioning
confidence: 84%
“…However, as also seen in Figure 1, with regard to pain the story is different, with literature over the past 5-6 years concluding that AT 2 R antagonists are analgesic, particularly in neuropathic pain and chronic inflammatory pain (Smith et al, 2016). On the other hand, there are also studies which indicate that AT 2 R agonists exert beneficial effects in pain (Bessaguet et al, 2018).…”
Section: Beneficial Actions Of At 2 R In Disease Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiotensin II is classically associated to vascular effects, which are mediated by activation of the angiotensin II type 1 receptor (AT1R). However, more recently, Ang II has been associated with pain sensitization during neuropathic pain induced by nerve injury, diabetis or herpes zoster, by an action on its receptor Ang II receptor type 2 (AT2R) (Anand et al., 2013; Bessaguet et al., 2018; Kim et al., 2019; Nemoto et al., 2015; Ogata et al., 2016; Rice et al., 2014; Shepherd, Copits, et al., 2018; Shepherd, Mickle, et al., 2018; Smith et al., 2016). AT2R antagonists have been successfully tested in pre‐clinical studies and, lately in clinical trials in patients with neuropathic pain (Ogata et al., 2016; Rice et al., 2014; Smith et al., 2016).…”
Section: Introductionmentioning
confidence: 99%